Neuromodulation Intervention in Resistant Depression - Era Catur Prasetya; Lestari Basoeki (Jurnal Psikiatri Surabaya, 2020)
Treatment-resistant depression occurs in about 20% of all Major Deppresion Disorder patients. In addition to the high cost of treatment to be borne, the high functional disability rate, the suicide rate triggered by the disorder is also quite large. Various efforts were made to overcome this, including dose optimization and duration of treatment, substitution of drug selection, combination therapy and augmentation using non-antidepressant drugs and bilateral electroconvulsion therapy. Current pharmacological options according to some experts are no more efficacious than the 1950s. Clearly, a novel therapeutic approach to treatment - resistant depression disorders is urgently needed. Over the last few decades, there has been a renewed interest in focal neuromodulation as a treatment approach for neuropsychiatric conditions. The neuromodulation-based interventions discussed include Transcranial Magnetic Stimulation (TMS) and Transcranial Direct Current Stimulation (tDCS), which are non invasive intervention therapy and Vagus Nerve Stimulation (VNS) and Deep Brain Stimulation (DBS), which are invasive interventional therapies. This literature review proves that, although today only TMS and VNS have been approved for use by the Food and Drug Administration (FDA) in the United States, but neuromodilation-based intervention therapy has proven to be promising as a more effective and efficient resistant depression therapy in the future.